Pemberdayaan Masyarakat Pada Masa Pandemi COVID-19 Melalui Lembaga PKBM (Pusat Kegiatan Belajar Masyarakat) Tuah Cahaya Berlian di Kecamatan Kundur Utara - Yesti Ulan Septianingsih; Ramadhani Setiawan; Edison Edison (Social Issues Quarterly, 2023)
This community empowerment is one of the efforts made by the government to provide awareness and also build capacity for community participation with sewing training activities during the co-19 pandemic. Efforts to empower the community can be carried out by providing a learning platform in the form of sewing training with these activities providing potential to the community, so that they can take advantage of their potential and can become independent human beings. This research method is to use a descriptive type method with a qualitative approach. Observation data collection techniques, interviews, and documentation. Data analysis techniques using data reduction, data presentation and drawing conclusions. This research aims to determine community empowerment through PKBM Tuah Cahaya Berlian in North Kundur District using 3 indicators from Wrihatnolo and Dwidjowijoto that the empowerment process is: awareness, capacity building, and empowering. The results of this study indicate that Community Empowerment Through PKBM (Center for Community Learning Activities) in North Kundur District has been optimal in its implementation. Even though it was optimal, it still caused problems for the PKBM participants, that is, there were those who could not measure clothes according to the pattern that had been made. This could be an inhibiting factor for PKBM Tuah Cahaya Berlian in Kundur Utara.